RELIGIOUS AUTHORITIES HEADING FOR 2024 ELECTIONS: Case Study on the PKB Party After the Ijtima Ulama Nusantara - Mutiullah, Muhammad (Jurnal Moderasi, 2023)
Abstract This research seeks to explore how the influence of the authority of religious leaders on Indonesian society. In this case, the religious leaders have excellent and credible religious knowledge and a strong societal influence. Indonesian people used to call them Kyai. This research raises several general questions: Does the authority of religious leaders only apply to matters of religious affairs? To what extent is the influence of the authority of religious figures (kyai) in Indonesian society? Do religious leaders also have a strong influence in the political sphere? If yes, why could it happen? This research will try to see the influence of Kyai's authority within the Partai Kebangkitan Bangsa (PKB) party. More specifically, this research will look at the influence of the Kyai in the PKB party after the Ijtima' Ulama Nusantara meeting. This meeting is one of PKB's political strategies to win the 2024 general election. This research will look at the influence of the authority of religious leaders within the PKB party ahead of the 2024 general election. The author argues that the authority of religious leaders in Indonesia applies not only to religious issues but also to all joints of the life of Indonesian society, including politics. The author also wants to argue that the authority of the kyai is used by the party to increase the electability of the party and gain support from the community. It is proven, among other things, after the Ijtima 'Ulama Nusantara event organized by the PKB party to win the 2024 general election. This research will collect written data from several works of literature and essential data in the form of information or news from the media. This research will use the theory of Clifford Geertz on religious experts as cultural brokers. Keywords: Kyai Authority, PKB, Ijtima' Ulama Nusantara